Major depressive disorder and access to health services among people who use illicit drugs in Vancouver, Canada - Tara Beaulieu; Lianping Ti; M.-J. Milloy; Ekaterina Nosova; Evan Wood; Kanna Hayashi (Substance Abuse Treatment, Prevention, and Policy, 2018)
Abstract Background People who use illicit drugs (PWUD) are commonly diagnosed with major depressive disorder (MDD). However, little is known about whether PWUD living with MDD experience additional barriers to accessing health services compared to those without MDD. We sought to identify whether MDD symptoms were associated with perceived barriers to accessing health services among people who use illicit drugs (PWUD) in Vancouver, Canada. Methods Data were collected through prospective cohorts of PWUD in Vancouver, Canada between 2005 and 2016. Using multiple logistic regression, we examined the relationship between MDD symptoms, defined as a Centre for Epidemiologic Studies Depression (CES-D) scale total score of ≥16, and barriers to access health services. We also used descriptive statistics to examine common barriers among participants who reported any barriers. Results Among a total of 1529 PWUD, including 521 (34.1%) females, 415 (27.1%) reported barriers to accessing health services, and 956 (62.5%) reported MDD symptoms at baseline. In multiple logistic regression analyses, after adjusting for a range of potential confounders, MDD symptoms (adjusted odds ratio [AOR] = 1.40; 95% confidence interval [CI]: 1.03–1.92) were positively and significantly associated with barriers to accessing health services. Among those who reported MDD symptoms and barriers to access, commonly reported barriers included: long wait lists/times (38.1%); and treated poorly by health care professionals (30.0%). Conclusion These findings show that the likelihood of experiencing barriers to accessing health services was higher among PWUD with MDD symptoms compared to their counterparts. Policies and interventions tailored to address these barriers are urgently needed for this subpopulation of PWUD.